Copper(II)‐Catalyzed Aminohalogenation of Alkynyl Carbamates. Issue 11 (15th March 2021) - Giofrè, Sabrina; Loro, Camilla; Molteni, Letizia; Castellano, Carlo; Contini, Alessandro; Nava, Donatella; Broggini, Gianluigi; Beccalli, Egle M.
Abstract: A useful aminohalogenation reaction for the cyclization of O ‐alkynyl carbamates under copper catalysis has been developed. N ‐Halosuccinimides have been used as a halogen source. The intramolecular C−N bond formation occurs selectively affording haloalkylidene substituted heterocycles. Just in the case of α, α‐cyclohexyl‐substituted propargyl carbamate, the alkoxyhalogenation pathway was operative. The mechanism for the two alternative reaction pathways was investigated by modeling the corresponding transition states at the DFT level. Abstract : The aminohalogenation reaction of O ‐alkynyl carbamates under copper catalysis has been developed. The intramolecular C−N bond formation occurs selectively affording haloalkylidene substituted heterocycles. In the case of α, α‐cyclohexyl‐substituted propargyl carbamate, the alkoxyhalogenation pathway was operative. The mechanism for the two alternative reaction pathways was investigated by modeling the corresponding transition states at the DFT level.